High Hydrostatic Pressure: A Green Extraction Technique for Food and Pharmaceutical Industries - Murat Altuner, Ergin (BENTHAM SCIENCE PUBLISHERS, 2023)
High Hydrostatic Pressure (HHP) is a green extraction method, which finds several uses in different branches of science. HHP is a novel non-thermal technique mostly used in food processing. The “high pressure” in HHP states an ultra-high cold isostatic hydraulic pressure, which processes basically at low or mild process temperatures (<45 °C) ranging between 100 and 800 MPa. In some applications, this pressure can extend up to 1000 MPa. In food processing, there are several purposes for using HHP, such as sterilizing, coagulating, and gelatinizing food samples. Alternatively, HHP has many remarkable uses in some branches of science besides food processing. This chapter aims to present the capabilities of HHP as a green extraction technique in the food and pharmaceutical industries.